IMF Managing Director's Statement to the Development Committee, April 2019. (Policy Papers; Policy Paper ;, 2019)
While growth in advanced economies is losing momentum amid trade tensions and policy uncertainty, activity in many emerging and low-income developing countries (EMDEs) has remained more robust, supported by still favorable financing conditions. Differences across EMDEs are large, however, and downside risks are building. Policy priorities include enhancing resilience in response to a more challenging global environment, creating fiscal space for essential development spending, containing debt vulnerabilities, and promoting strong and inclusive growth. Strengthening revenue generating capacity, enhancing public spending efficiency, and addressing infrastructure gaps are critical for reaching the 2030 Sustainable Development Goals.